Case series of isolated primary persistent sciatic vein - Tanop Srisuwan (2018)
Our study aimed to present a short series on the persistent sciatic vein, a rare venous variation, without Klippel-Trenaunay-Weber syndrome and to review the anatomical consideration of deep venous systems. Four cases of lower-type persistent sciatic vein were found. A combination of May-Thurner syndrome and persistent sciatic vein was found in 2 cases. Non-hypoplastic femoral veins, normal and duplicated, were found in 3 cases. This study concluded that in this persistent sciatic vein, the associated non-hypoplastic femoral vein is not uncommon, and care must be taken about this condition during ultrasonographic examination. Unusual causes of chronic venous insufficiency and other venous anomalies should not be overlooked. © 2013 The Author(s).